Intragenic CpG Islands and Their Impact on Gene Regulation - Cain, James A.; Montibus, Bertille; Oakey, Rebecca J. (Frontiers in Cell and Developmental Biology, 2022)
The mammalian genome is depleted in CG dinucleotides, except at protected regions where they cluster as CpG islands (CGIs). CGIs are gene regulatory hubs and serve as transcription initiation sites and are as expected, associated with gene promoters. Advances in genomic annotations demonstrate that a quarter of CGIs are found within genes. Such intragenic regions are repressive environments, so it is surprising that CGIs reside here and even more surprising that some resist repression and are transcriptionally active within a gene. Hence, intragenic CGI positioning within genes is not arbitrary and is instead, selected for. As a wealth of recent studies demonstrate, intragenic CGIs are embedded within genes and consequently, influence ‘host’ gene mRNA isoform length and expand transcriptome diversity.